Comparison of the thermodynamic stabilities and solution conformations of DNA.RNA hybrids containing purine-rich and pyrimidine-rich strands with DNA and RNA duplexes. - Gyi, J; Conn, G; Lane, A; Brown, T (1996)
The conformations and thermodynamic stabilities of duplexes containing purine-rich (GAA-GAGAAGC) and pyrimidine-rich (GCTTCTCTTC or GCUUCUCUUC) DNA and RNA strands have been measured by UV melting, electrophoresis, circular dichroism, and NMR spectroscopy. The free energies of stabilization (-delta G) were in the order rR.rY > rR.dY > dR.dY > dR.rY. The two DNA.RNA hybrid duplexes showed conformational properties intermediate between those of DNA.DNA and RNA.RNA duplexes and also different from one another. Differences between 1H chemical shifts of the DNA strands in the two hybrid duplexes and those of the DNA duplex were larger than analogous shift differences for the RNA protons, and the differences were larger for the purine than the pyrimidines in the DNA strands. Detailed analysis of the nucleotide conformations using both NOE and scalar coupling data showed that the sugar conformations of the ribonucleotides are all near C3'-endo. The deoxyribonucleotides were in the "S" domain, i.e., near C2'-endo in the DNA duplex, and C1'-exo to C2'-endo in the two hybrids. However, the deoxyriboses in the two hybrids appear more flexible than in the DNA duplex, with the fraction in the "N" (C3'-endo) state increasing in the order dR.dY < dR.rY < rR.dY. Globally, the pure DNA duplex was B-form and the pure RNA duplex A form. The two DNA.RNA hybrids were neither A nor B, but closer globally to the A than the B form. The less stable dR.rY duplex has a significantly different conformation from rR.dY both at the local nucleotide level and globally.